Wide Operating Range Minimum Phase Interleaved Hybrid Converter with Reduced Leakage Current - Samal S.K.; Bussa V.K.; Singh R.K.; Mahanty R. (My University, 2025)
In order to minimize the common mode leakage current and capability to supply both dc and ac outputs simultaneously, a transformerless wide operating range minimum phase interleaved hybrid converter for photovoltaic applications is presented in this article. The proposed hybrid converter has wide operating ranges of duty ratio (D) and modulation index (Mi), and can be operated at both the conditions, D + Mi ≥ 1 and D + Mi ≤ 1, which increases the dc gain and improves the ac output quality. Moreover, the proposed hybrid converter exhibits minimum phase behavior as the right half plane zero is eliminated, which enables simpler controller design and facilitates improved bandwidth with higher load current. A hybrid pulsewidth modulation technique is developed for the proposed hybrid converter to minimize the high-frequency common mode voltage terms of the parasitic capacitor and to regulate both the dc and ac outputs simultaneously. The performance of the proposed hybrid converter is compared with other similar topologies to bring out its advantages. Detailed mathematical modeling of the proposed hybrid converter is carried out and a 930-W laboratory prototype is developed to verify its performance. © 1972-2012 IEEE.